Water table effects on bean yield and nitrate distribution in the soil profile - Saad, João Carlos Cury [UNESP]; Calegaro, J. C. [UNESP] (My University, 2004)
In order to evaluate the bean yield under different water table levels as well as the moisture and nitrate distribution in the soil profile, a field experiment was carried out at the experimental area from the College of Agronomic Sciences - UNESP, Botucatu, SP, Brazil. Beans were grown in field lysimeters and subjected to five water table depths:30; 40; 50; 60 and 70 cm. The moisture in the soil profile was gravimetrically determined through samples obtained at 10; 20; 30; 40; 50; 60 and 70cm of depth. The water table depths of 30cm and 40cm showed the highest productivities (3,228.4 kg.ha-1 and 3,422.1 kg.ha-1, respectively), showing no statistical differences between each other. The highest productivity was related to the two most elevated water table levels (30 and 40cm), which provided the highest moisture average values on basis of volume in the soil profile (33.3 e 31%) as well as the consumptive use of water (416 and 396 mm). The nitrate content during the bean cycle at the extraction depth of 60cm has been under the safe drinking limit of 10 mg.1-1 for water table depths of 30; 40; 50 and 60cm, showing the denitrification effectiveness as a way of controlling water table from nitrate pollution. The water table handling allowed the attainment of high bean productivity levels, as well as the reduction of the nitrate level.
Keywords: Bean; Denitrification; Lysimeters; Nitrate; Soil moisture; Water table; Agronomy; Nitrates; Soils; Water analysis; Bean cycle; Nitrate levels; Crops; Ceratonia; Soil; Water Table